Molecular and Structural Characterization of MHC Class II β Genes Reveals High Diversity in the Cold-Adapted Icefish Chionodraco hamatus - Buonocore, Francesco; Gerdol, Marco; Lucente, Daniela; Poerio, Elia; Scapigliati, Giuseppe; Cimmaruta, Roberta; Mattiucci, Simonetta; Pallavicini, Alberto (Scientific Reports, 2019)
M. Gerdol, D. Lucente, F. Buonocore , E. Poerio, G. Scapigliati, S. Mattiucci, A. Pallavicini, R. Cimmaruta Molecular and structural characterization of MHC class II b genes reveals high diversity in the cold-adapted icefish Chionodraco hamatus Scientific reports (2019), 9: 5523. Research was performed under the Italian Program of Antarctic Research (PNRA), granted projects PNRA13_ AZ01.09, PNRA16_00099 and PNRA16_00279.